Effect of erythropoietin on staurosporine-induced apoptosis and differentiation of SH-SY5Y neuroblastoma cells - Pregi, N. (2006)
Since apoptosis appeared to be related to neurodegenerative processes, neuroprotection has been involved in investigation of therapeutic approaches focused upon pharmacological agents to prevent neuronal programmed cell death. In this regard, erythropoietin (Epo) seems to play a critical role. The present work was focused on the study of the Epo protective effect upon human neuroblastoma SH-SY5Y cells subjected to differentiation by staurosporine. Under this condition, profuse neurite outgrowth was accompanied by programmed cell death (35% of apoptotic cells by Hoechst assay, showing characteristic DNA ladder pattern). A previous treatment with recombinant human Epo (rHuEpo) increased the expression of the specific receptor for Epo while prevented apoptosis. Simultaneously, morphological changes in neurite elongation and interconnection induced by staurosporine were blocked by Epo. These Epo effects proved to be associated to the induction of Bcl-xL at the mRNA and protein levels (RT-PCR and Western blot after immunoprecipitation) and were mediated by activation of pathways inhibited by wortmannin. In conclusion, the fact that both events induced by staurosporine, cell apoptosis and differentiation, were prevented in SH-SY5Y cells previously exposed to rHuEpo suggests interrelated signaling pathways triggered by the Epo/EpoR interaction. © 2005 Elsevier B.V. All rights reserved.